THE ROLE OF MINDFULNESS-BASED COGNITIVE THERAPY (MBCT) IN ENHANCING SELF-ESTEEM AMONG MINORITY ETHNIC ADOLESCENTS: A LITERATURE REVIEW - Yansi Larbona; Susi Fitri; Eka Wahyuni (LP2M IAI Al-Khairat Pamekasan, 2026)
Adolescence is a critical developmental stage characterized by increased vulnerability to psychological challenges, particularly among individuals from minority ethnic backgrounds. Experiences of discrimination and social exclusion may negatively affect adolescents’ self-esteem and identity development. Therefore, identifying effective interventions to support their psychological well-being is essential. This study aims to explore the role of Mindfulness-Based Cognitive Therapy (MBCT) in enhancing self-esteem among adolescents with minority ethnic identities. This study employed a narrative literature review design, analyzing 10 selected articles published between 2012 and 2024. The literature search was conducted using academic databases, including Google Scholar and Sage Journals, with keywords related to MBCT, self-esteem, adolescents, and ethnic minority. The selected studies were analyzed using a thematic analysis approach to identify key patterns and relationships. The findings reveal that self-esteem among minority adolescents is influenced by a complex interaction of developmental factors, ethnic identity, and experiences of discrimination. Discrimination consistently emerges as a significant risk factor, while ethnic identity and supportive environments function as protective factors. MBCT demonstrates potential as an effective intervention by enhancing self-awareness, emotional regulation, and adaptive coping strategies, thereby helping adolescents manage the psychological impact of discrimination. In conclusion, MBCT offers a promising approach to improving self-esteem among adolescents with minority ethnic identities. However, its effectiveness depends on the presence of inclusive and culturally sensitive environments. Future research should focus on context-specific applications, particularly in non-Western settings.